2017
DOI: 10.1038/s41598-017-11030-5
|View full text |Cite|
|
Sign up to set email alerts
|

Structural and pharmacological basis for the induction of mitochondrial biogenesis by formoterol but not clenbuterol

Abstract: Mitochondrial dysfunction is associated with numerous acute and chronic degenerative diseases. The beta-2 adrenergic receptor (β2AR) agonist formoterol induces mitochondrial biogenesis (MB), but other β2AR agonists, such as clenbuterol, do not. We sought to identify the MB signaling pathway of formoterol and the differences in signaling between these two ligands that result in the differential induction of MB. While formoterol and clenbuterol increased cAMP, only formoterol increased the phosphorylation of Akt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 50 publications
2
26
0
Order By: Relevance
“…Based on increases in mtDNA and mitochondrial gene and protein expression, our studies have shown that formoterol induces MB in the kidney, heart, skeletal muscle, and spinal cord of mice, while clenbuterol has not been found to induce MB. 26,27,32,55 Recent work from our laboratory has attributed this difference to unique structural features of the two agonists resulting in distinct receptor-ligand interactions and divergent signaling pathways. Specifically, formoterol is able to extend across the ADRB2 binding pocket, leading to activation of the Gbc-Akt-eNOS-sGC pathway, which is necessary for the induction of MB; clenbuterol and other non-mitochondrially biogenic ADRB2 agonists do not activate this pathway.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on increases in mtDNA and mitochondrial gene and protein expression, our studies have shown that formoterol induces MB in the kidney, heart, skeletal muscle, and spinal cord of mice, while clenbuterol has not been found to induce MB. 26,27,32,55 Recent work from our laboratory has attributed this difference to unique structural features of the two agonists resulting in distinct receptor-ligand interactions and divergent signaling pathways. Specifically, formoterol is able to extend across the ADRB2 binding pocket, leading to activation of the Gbc-Akt-eNOS-sGC pathway, which is necessary for the induction of MB; clenbuterol and other non-mitochondrially biogenic ADRB2 agonists do not activate this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, formoterol is able to extend across the ADRB2 binding pocket, leading to activation of the Gbc-Akt-eNOS-sGC pathway, which is necessary for the induction of MB; clenbuterol and other non-mitochondrially biogenic ADRB2 agonists do not activate this pathway. 32 Therefore, despite both formoterol and clenbuterol being ADRB2 agonists, dissimilar structures and signaling leading to MB with formoterol has a greater therapeutic potential for the management of SCI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We reported that formoterol treatment restored renal function with concomitant increases in mitochondrial protein expression and function after AKI in mice (Jesinkey et al, 2014). We also elucidated the mechanism of formoterol-induced MB in RPTCs (Cameron et al, 2017). ABBREVIATIONS: AKI, acute kidney injury; b 2 AR, b-2 adrenergic receptor; DMSO, dimethylsulfoxide; Drp1, dynamin-related protein 1; IRI, ischemia-reperfusion injury; KIM-1, kidney injury marker-1; KO, knockout; MB, mitochondrial biogenesis; Mfn2, mitofusin 2; NDUFS1, NADH: ubiquinone oxidoreductase core subunit S1; PCR, polymerase chain reaction; PGC-1a, peroxisome proliferator-activated receptor gamma coactivator-1a; RPTC, renal proximal tubule cell; SCr, serum creatinine; WT, wild-type.…”
Section: Introductionmentioning
confidence: 86%